Demon seed - Koontz, Dean R., 1945- (Berkley Books, 1997)
Susan Harris lived in self-imposed seclusion, in a mansion featuring numerous automated systems controlled by a state-of-the-art computer. Every comfort was provided, and in this often unsafe world of ours, her security was absolute.